Identifying sea level rise vulnerability using GIS development of a transit inundation modeling method. - Oswald, M.R (International Journal of Geoinformatics)
Sea level rise inundation poses risk to critical transportation infrastructure as the threat of climate change continues. Although mitigation efforts are being implemented, these practices are not timely enough to avoid all potential impact. Therefore, adapation practices are essential to building resilience and protecting transportation facilities, specifically public transit (rail and bus) networks. This research establishes a method, Transit Inundation Modeling Method (TIMM), used to identify transit infrastructure systems that are vulnerable to sea level rise using Geographic Information Systems (GIS). TIMM allows transit agencies to begin adapting by identifying at risk links and nodes based on various sea level rise inundation levels. This method is applied to a case study application on the Philadelhia County transit system (railway and bus routes). This case study is used to determine the method's applicability and relevance to a real world transit network. By using this method to identify vulnerabilities, transit agencies throughout the nation can begin to implement adaptation practices (elevate, relocate or reinforce) in order to protect existing facilities as well as plan for future transit projects.